Determinants of gang affiliation in Singaporean youth offenders: social and familial factors. Issue 1 (12th January 2015) - Chu, Chi Meng; Daffern, Michael; Thomas, Stuart; Yaming, Ang; Long, Mavis; O'Brien, Kate
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Gang affiliation in youth is associated with increased criminal recidivism and an exaggeration of various criminogenic needs; affiliation also meets a variety of youth's personal and social needs. The purpose of this paper is to describe a study of the self-reported reasons for joining and leaving gangs, as well as the difficulties faced by Singaporean youth offenders in leaving youth gangs; it also explores the relationship between gang affiliation and family connectedness, educational attainment and early exposure to gangs. Design/methodology/approach – This prospective study involved structured interviews and administration of questionnaires with 168 youth offenders in Singapore. Univariate and multivariate analyses were conducted to examine the research questions. Findings – Gang-affiliated youth cited a desire to establish and maintain friendships as their primary reasons for joining a gang. Youth who left their gang reported maturing beyond this need and the activities of their gang, particularly in light of the deleterious impact of their gang-related activities on familial relationships and employment and financial status. Early exposure to gangs through family and neighborhood influences, and poor educational engagement increased the likelihood that youth would join a gang. Practical implications – This study highlights the need for clinicians and other service providers to better understand the universal human needs that are met through gang affiliation and the correlates of affiliation. Originality/value – Few studies have directly examined the factors relating to gang affiliation in a non-western context; this study may be relevant to professionals working in the juvenile justice and offender rehabilitation arenas.